Aviation and the COVID-19 Pandmic: Flying to the 'Next Normal' - Peter James Rimmer (Journal of International Trade, Logistics and Law, 2020)
An account is given of the effect of the novel COVID-19 pandemic on the global commercial aviation industry in September 2020. Recurrent features of the effects of past crises upon the aviation industry since the Second World War are identified before proceeding to gauge if they can be recognized in the current situation. This analysis is aided by pinpointing key elements of the aviation ecosystem: demand, airlines, airports, network connectivity and governance. Each of these elements are examined in turn in September 2020, before proceeding to determine how they will fare once an effective vaccine is introduced, and the pandemic is over. Then attention is given to how logisticians and corporate strategists can contribute to the realization of the ‘next normal’ by benchmarking and monitoring the recovery